Airway to the East 1918-1920 and the collapse of no. 1 aerial route RAF - Semple, Clive (Pen & Sword Aviation, 2012)
The origins of what became officially known as No 1 Aerial Route lay in the newly formed Royal Air Force's desire to move several squadrons of the then recently designed first heavy bomber to enter service - the Handley Page O/400 - to the war in the Middle-East. In summer 1919, a fleet of fifty-one bombers left England and France to fly to Cairo. Seventeen of these aircraft were destroyed or crashed en-route. Eight airmen were killed. A Court of Enquiry was held at the Air Ministry to investigate; however, the findings were suppressed by the Secretary of State for Air, Winston Churchill.